Environmental Impacts of Intensive Cardamom (Small) Cultivation in Indian Cardamom Hills: The Need for Sustainable and Efficient Practices - Paddu Krishnappa Shetty1, Raju Ravi2, Alappan Subbiah3, Murigendra B. Hiremath1, Muthusamy Murugan1*, (Recent Research in Science and Technology, 2011)
The recent intensification of small cardamom (Elettaria cardamomum Maton) farming, and the prospects of intensification, will have the major detrimental impacts on the Indian cardamom hills (ICH) ecosystem. The increased (4 fold) cardamom production during the past 30 years was associated with a several fold increase in the consumption of fertilizers and pesticides as well as drastic reduction in erstwhile rainforest land and canopy cover. Based on simple linear extension of past trends, and the anticipated future demand of cardamom would be associated with approximately 3 fold increase in both nitrogen and phosphorus fertilizer rates as well as pesticides ( 4-5 fold increase in number of spray rounds) and further reduction in forest canopy cover (40%). These projected changes would have dramatic impacts on the functioning of the cardamom ecosystem because of complete loss of biodiversity and land and forest degradation. The largest impacts would be on fresh water ecosystem, which would be greatly eutrophied by high rates of nitrogen and phosphorus release from cardamom and tea plantations, and contaminated with various toxic pesticides. These detrimental environmental impacts of intensive cardamom agriculture can be minimized only if there is much more efficient use and recycling of nutrients between forest and soil.